Action research and adherence to antihypertensive therapy in the family context - Lima, Gabriela de Sousa (2021)
This is a qualitative study, using action research carried out in the interior of the state of Ceará, between September 2018 and October 2019. It aied to identify factors that interfere with adherence to treatment for hypertension and proposing educational strategies in the family context that would contribute to its improvement. The participants were four adult members of the same family, of which two suffered from hypertension and two who did not. Eight home visits were carried out with actions ranging from: needs assessment to health education. The interviews were audio-recorded and some observation data were included in a field diary. Data were interpreted by content analysis. Three thematic units emerged and eight units of meaning: Factors that hinder antihypertensive treatment (Use of medication as a complicating factor in the treatment; Inadequate eating habits; Comorbidities in justifying sedentary lifestyle); Knowledge about antihypertensive treatment (Formal and informal knowledge; and Assessment of interventions and home visits) and Outcomes of educational interventions. Factors interfering with treatment adherence were deficient knowledge, inappropriate diet, failure to use medication and lack of physical activity. The evaluation after interventions showed improvement in family knowledge about hypertension and complications, decreased sodium consumption and increased adherence to physical activity. Follow-up educational interventions, agreed by the family, promoted reflections and lifestyle changes with a positive impact on adherence to antihypertensive treatment.